Lightlike hypersurfaces in semi-Riemannian manifold with semi-symmetric non-metric connection - Yasar, Erol; Cöken, A. Ceylan; Yücesan, Ahmet (MATHEMATICA SCANDINAVICA, 2008)
In this paper, we study lightlike hypersurfaces of a semi-Riemannian manifold admitting a semi-symmetric non-metric connection. We give the equations of Gauss and Codazzi. Then, we obtain conditions under which the Ricci tensor of a lightlike hypersurface is symmetric given that the ambient space is equipped with a semi-symmetric non-metric connection.